PENGARUH NUSAMUSIC DIGITAL EXPLORER BERBASIS AUGMENTED REALITY DALAM PEMBELAJARAN SENI MUSIK UNTUK MENINGKATKAN HASIL BELAJAR PADA KELAS V SD - Sinaga, Ruth Silvia; Sumartiningsih, Sri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the effect of NusaMusic Digital Explorer based on Augmented Reality (AR) in music learning to improve students’ learning outcomes in grade V of elementary school. The research was motivated by the low learning outcomes and limited use of instructional media in teaching traditional musical instruments. This study employed a quantitative approach with an experimental method using a one-group pretest-posttest design. The sample consisted of 25 fifth-grade students at SDN Majalengka Wetan VIII selected through purposive sampling. Data were collected using multiple-choice tests consisting of 20 items that had been tested for validity and reliability. Data analysis was conducted using descriptive and inferential statistics, including normality test, homogeneity test, and t-test. The results showed that the average pretest score was 58.8, while the posttest score increased to 87.22. The hypothesis testing indicated that t-count (4.71) was greater than t-table (2.11), which means there is a significant effect of the use of NusaMusic Digital Explorer based on Augmented Reality on students’ learning outcomes. The normalized gain (N-Gain) score was 0.69, categorized as moderate to high improvement. The findings indicate that the use of AR-based learning media can enhance students’ engagement, motivation, and understanding through interactive, visual, and auditory experiences. Therefore, NusaMusic Digital Explorer can be considered an effective and innovative learning media in improving music learning outcomes in elementary education.